2020
DOI: 10.2147/ceg.s264812
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of Novel Therapeutic Molecular Targets in Inflammatory Bowel Disease by Using Genetic Databases</p>

Abstract: Purpose: Utilization of genetic databases to identify genes involved in ulcerative colitis (UC), Crohn's disease (CD), and their extra-intestinal manifestations. Methods: Protein coding genes involved in ulcerative colitis (3783 genes), Crohn's disease (3980 genes), uveitis (1043 genes), arthritis (5583 genes), primary sclerosing cholangitis (PSC) (1313 genes), and pyoderma gangrenosum (119 genes) were categorized using four genetic databases. These include Genecards: The Human Gene Database (www.genecards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Mohan et al [ 99 ] reported using genetic databases to find new molecular targets for IBD. They used four different genetic databases to categorize the protein-coding genes associated with UC (3783 genes), CD (3980 genes), uveitis (1043 genes), arthritis (5583 genes), primary sclerosing cholangitis (1313 genes), and pyoderma gangrenosum (119 genes).…”
Section: Role Of Computational Methods In Ibd Drug Discoverymentioning
confidence: 99%
“…Mohan et al [ 99 ] reported using genetic databases to find new molecular targets for IBD. They used four different genetic databases to categorize the protein-coding genes associated with UC (3783 genes), CD (3980 genes), uveitis (1043 genes), arthritis (5583 genes), primary sclerosing cholangitis (1313 genes), and pyoderma gangrenosum (119 genes).…”
Section: Role Of Computational Methods In Ibd Drug Discoverymentioning
confidence: 99%
“…Notably, the activities of the 3 key enzymes participating in the leukotriene pathway, namely, 5-lipoxygenase, 5-lipoxygenase-activating protein, and leukotriene A4 hydrolase, were markedly increased in the lesions of patients with active IBD, indicating that an elevated LTB4 release may contribute to neutrophil accumulation during IBD. 50 , 51 In addition, genetic depletion of 5-lipoxygenase or neutralization of 5-lipoxygenase with zileuton is associated with significant amelioration of experimental colitis. 52 Another arachidonic acid metabolite, hepoxilin A3 (HXA3), a well-known neutrophil chemotactic agent, is released from the apical surface of the epithelium to drive neutrophils to migrate across the epithelium into the gut lumen.…”
Section: The Intestinal Epithelium Recruits Neutrophils To Sites Of I...mentioning
confidence: 99%
“…There are also studies investigating the upstream regulation of IL-25. Though the IL-25 gene is located at 14q11.2 within the CD susceptibility locus [ 86 ] and was proved to be associated with CD and UC by analysis of genetic databases [ 87 ], no significant difference concerning its coding regions (c424C/A) was found between IBD patients and controls [ 86 ]. Thus, other factors involved in the transcription of IL-25 resulting in aberrant amounts of IL-25 in IBD patients have been further investigated.…”
Section: Introductionmentioning
confidence: 99%